The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/pc.26998
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of AA 2024T3 fiber metal laminate with nanosilica‐reinforced epoxy based polymeric composite panel for lightweight applications

Abstract: Fiber metal laminates (FMLs) are a hybrid composite material used in aircraft structural parts. They are fabricated by stacking thin aluminum sheets with a fiber-reinforced polymer composite. In this research work, nanosilica was mixed with epoxy resin in different weight percentages such as 0, 1, 3, 5, and 7 wt% for the preparation of FML. Nanosilica was used as a secondary reinforcement in the epoxy resin to improve the interfacial bonding and mechanical strength of the FML. The morphology and chemical compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…FMLs were fabricated using aluminum sheets having two different kinds of surface pre‐treatments (mechanical and chemical). Mechanical pre‐treatment of aluminum surfaces was carried out by subjecting them to mechanical abrasion using various grades of silicon carbide grit papers (P80 and P180) to remove the loosely adherent oxides and introduce roughness on the aluminum surface 31,32 . The residual metal debris on the abraded aluminum surfaces was cleaned with acetone to remove unwanted contaminants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FMLs were fabricated using aluminum sheets having two different kinds of surface pre‐treatments (mechanical and chemical). Mechanical pre‐treatment of aluminum surfaces was carried out by subjecting them to mechanical abrasion using various grades of silicon carbide grit papers (P80 and P180) to remove the loosely adherent oxides and introduce roughness on the aluminum surface 31,32 . The residual metal debris on the abraded aluminum surfaces was cleaned with acetone to remove unwanted contaminants.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanical pre-treatment of aluminum surfaces was carried out by subjecting them to mechanical abrasion using various grades of silicon carbide grit papers (P80 and P180) to remove the loosely adherent oxides and introduce roughness on the aluminum surface. 31,32 The residual metal debris on the abraded aluminum surfaces was cleaned with acetone to remove unwanted contaminants. For chemical pre-treatment, the aluminum sheets were immersed in 100 g/L sodium hydroxide (NaOH) solution at 60 C for 10 min after the mechanical abrasion process.…”
Section: Preparation Of Fmlsmentioning
confidence: 99%
“…In most of the literature AA 2024-T3 has been used for the fabrication of FMLs. 7,[32][33][34][35][36][37][38][39] Few of the researchers have also used other grades of aluminum alloys such as AA 1050, [40][41][42] AA 1060-H12, 43 AA 1200-H14, 44 AA 2024-O, 45 AA 5005, 46 AA 5052-O, 47 AA 5052-H32, [48][49][50] AA 6061-T6, 17,29,51,52 AA 6063-T6, 53 and AA 7075-T6. 52,54,55 Limited amount of work has been conducted on the Magnesium alloy, 56,57 Titanium, 45 and Steel.…”
Section: Research Gap Addressed In the Papermentioning
confidence: 99%
“…On a component level application, Wang et al 31 established a multi‐objective integrated optimization framework considering for the fabrication of a tapered rim composed of CFRP rim and aluminum alloy spoke. In most of the literature AA 2024‐T3 has been used for the fabrication of FMLs 7,32–39 . Few of the researchers have also used other grades of aluminum alloys such as AA 1050, 40–42 AA 1060‐H12, 43 AA 1200‐H14, 44 AA 2024‐O, 45 AA 5005, 46 AA 5052‐O, 47 AA 5052‐H32, 48–50 AA 6061‐T6, 17,29,51,52 AA 6063‐T6, 53 and AA 7075‐T6 52,54,55 .…”
Section: Research Gap Addressed In the Papermentioning
confidence: 99%
“…1 FMLs have been initially applied in the aerospace industry, such as Glare ® and CARALL ® , which were fabricated by glass or carbon fiber reinforced thermoset composites and aluminum layers. [2][3][4][5][6] It has been reported that FMLs not only possess excellent fatigue resistance and high strength of FRP but also maintain the ductility of metal materials with high specific stiffness, low crack propagation, and good dynamic properties. [7][8][9] In general, the traditional and commercial FMLs are based on fiber-reinforced thermosetting resins (i.e.…”
Section: Introductionmentioning
confidence: 99%